Immunothrombosis in cancer patients: contribution of neutrophil extracellular traps, ADAMTS-13 and von Willebrand factor - E. V. Slukhanchuk; V. O. Bitsadze; A. G. Solopova; J. Kh. Khizroeva; V. I. Tsibizova; J.-K. Gris; I. Elalamy; D. V. Shcherbakov; L. L. Pankratyeva; L. A. Ashrafyan; A. D. Makatsariya (Акушерство, гинекология и репродукция, 2023)
Introduction. Neutrophil extracellular traps (NETs) and von Willebrand factor (vWF) are integral players in thrombosis and inflammation in cancer patients. It has been increasingly evident that an active interplay exists between NETs and vWF. Some studies suggest that NETs cause decrease in ADAMTS-13 (a disintegrin and metalloprotease with thrombospondin type 1 motif, member 13) activity, being an arm in the pathogenesis of both thrombotic microangiopathies (TMA) and other thrombotic complications during oncological process.Aim: to assess a crosstalk between NETs, vWF, and ADAMTS-13 in uterine, ovarian, breast malignant neoplasms as well as cervical canal adenocarcinoma.Materials and Methods. From September 2019 to July 2022, a prospective controlled interventional non-randomized study was carried out with 106 patients hospitalized for planned surgical treatment aged 30 to 72 years. The main group included 73 patients with malignant neoplasms of the female genital organs and mammary glands, stage I–III: uterine cancer (subgroup 1; n = 18), ovarian cancer (subgroup 2; n = 21), cervical cancer – adenocarcinoma of cervical canal (subgroup 3; n = 9) and breast cancer (subgroup 4; n = 25). The control group consisted of 33 women with female genital tract and breast benign neoplasms. In all patients, serum levels of vWF, citrullinated histone H3 (citH3), MPO (myeloperoxidase) antigen, ADAMTS-13 activity, ADAMTS-13 antigen, and D-dimer were evaluated.Results. The study revealed significant differences in the concentration of NETosis markers between the main and control groups. Patients with uterine cancer and adenocarcinoma of the cervical canal peaked at NETosis markers. At the same time, there were significant differences in citH3 concentration among patients with «early» (stage I) and «not early» (stage II–III) disease forms. While assessing level of von Willebrand factor (vWF:Ag), antigen (ADAMTS-13:Ag), and ADAMTS-13 activity (ADAMTS-13:Ac), significant differences were found between the main and control groups (p < 0.0001). The vWF in the main groups was sharply increasedwhereas ADAMTS-13 antigen concentration and activity were decreased. A сorrelation analysis among oncological patients in main group showed that while citH3 level increased, it was also paralleled with rise in vWF:Ag (ρ = 0.80; p < 0.01) and MPO:Ag (ρ = 0.87; p < 0.01); increase in MPO:Ag level was coupled to rise in vWF:Ag (ρ = 0.70; p< 0.01), but increase in vWF:Ag occurred along with decline in ADAMTS-13:Ac (ρ = –0.43; p < 0.01) and ADAMTS-13:Ag (ρ= –0.42; p < 0.01).Conclusion. The interplay between NET, vWF, and ADAMTS-13 leads to a vicious circle, reduces ADAMTS-13 activity by increasing serum vWF concentration, which positively correlates with severity and mortality in TMA, acute ischemic infarction, and COVID-19. Targeting the NETs-vWF axis may pave the way for therapeutic strategies for immunothrombosis in various diseases, including cancer.